ARABIC LANGUAGE LEARNING INNOVATION: MANHAJI SONGS AS AN MEDIUM - Zikrullah Nuzuli Zikrullah Nuzuli (Jurnal Ikhtibar Nusantara, 2024)
The Manhaji method uses songs as an innovative medium for learning Nahwu and Shorof. This study aims to examine the implementation and effectiveness of the Manhaji method at Pondok Pasantren Al-Fitiyan, Tibang Syiah Kuala Banda Aceh. A descriptive qualitative approach was used with data collection techniques through observation, interviews, and documentation. The results showed that this method creates a pleasant learning atmosphere, increases learning motivation, and makes it easier for students to memorise and understand the rules of Nahwu and Shorof. Songs with interesting rhythms are effective tools in improving memory and retention of material. This research is expected to contribute to the development of more innovative and effective Arabic learning methods in pesantren throughout Aceh.